Kinematics, strain patterns, rheology, and geochronology of Woka ductile shear zone: Product of uplift of Gangdese batholith and Great Counter Thrust activity. (17th September 2020) - Feng, Yipeng; Wang, Genhou; Meng, Yuanku; Li, Dian; Xu, Xuming; Lu, Yang; Li, Jie; Liu, Han
Abstract : The Woka ductile shear zone is located at the southern margin of the middle section of the Gangdese magmatic belt and southeast of Lhasa. This article is a systematic study of the Woka ductile shear zone and provides kinematics, strain patterns, rheology, temperature environment, and geochronological data of the shear zone, which have great significance for understanding of the uplift and extension process of the southern section of the Gangdese. All shear indicators, such as asymmetrical folds, rotated porphyroclasts, and S–C fabrics, developed in the shear zone indicate the shear sense of top‐to‐the‐northwest with the shear nature of detachment. Mineral deformation thermometer and EBSD quartz fabric analysis indicate that the shear zone has experienced early high‐temperature (550–650°C) deformation and post‐superimposed low temperature (380–420°C) deformation. The differential stress (σ) of the ductile shear zone was 28.08–46.73 MPa. Strain rates (έ) ranged from 10 −10 to 10 −14 s −1 under a high‐temperature environment (600°C) and 10 −12 to 10 −16 s −1 under a low‐temperature environment (420°C). Three‐dimensional strain ellipsoid measurements of the Woka ductile shear zone indicate that all deformed samples appear as prolate ellipsoids (LS‐type tectonites), which represent an elongate strain. The average kinematic vorticity of the Woka ductile shear zone is 0.93, implying that the shear zone was dominated by simple shear. The thickness of the ductile shear zone was reduced by 12–28%. Combined with the U–Pb zircon age of the protolith of granitic protomylonite, the 40 Ar/ 39 Ar sericite age of granitic mylonite (22.38 ± 0.31 Ma) can represent the shear age. The Woka shear zone studied in this article may have been formed by the Great Counter Thrust (GCT) activity and uplift of the Gangdese batholith during the transforming period of the Lhasa Terrane from extrusion to a lateral extension. Abstract : Kinematics, strain pattern, rheology, and geochronology of the Woka ductile shear zone as a product of uplifting of the Gangdese Batholith and thrusting of the Great Counter Thrust (GCT) were studied. Three‐dimension strain ellipsoid data of the shear zone indicate that the shear zone was dominated by simple shear and the thickness of the ductile shear zone is reduced by 12–28%. The 40 Ar/ 39 Ar sericite age of granitic mylonite (22.38 ± 0.31 Ma) can represent the shear age.